Strategies for Developing the 21st Century Skills of School Principals under Loei Primary Educational Service Area Office - Phonsa, Kongnaren; Sroinam, Somkid; Phongphinyo, Phongnimit (Asian Journal of Education and Training, 2019)
In the 21st century, school leaders are expected to make school administration go smoothly including develop teaching and learning. School administrators must have a feature and skills that are outstanding and different from the previous school administrators. The purposes of this research were to study the 21st century skills of the principals, construct the development strategies, and evaluate the development strategies of the 21st century skills of the principals under Loei Primary Educational Service Area Office, Thailand. The participants consisted of 9 experts and 203 school administrators. The 5-rating scale questionnaire, structured interviews and experts meeting were employed for data collecting. The quantity data were analyzed by using SWOT analysis, PNIModified technique, and descriptive statistics and the qualitative data was analyzed by using content analysis. The results led to understand the characteristics of strategies for developing the 21st century skills of the school principals in primary schools and the research application was discussed.